The Extended Theory of Planned Behavior (TPB) to Analyze the Batik Purchase Intention of Indonesian Millennials and Gen Z - Indah Sepwina Putri; Annisa Dewi Akbari (Universitas Atma Jaya Yogyakarta, 2021)
As the nation’s cultural heritage of Indonesia, batik has an important role in the Indonesian economy. This industry provides job opportunities that involve a lot of human resources in it and contributes to the country's foreign exchange through the export of national batik to big countries. Although the development of the batik industry has increased, there are still problems in marketing batik products in Indonesia. These problems can lead to more serious problems such as batik craftsmen leaving the business. These problems must be overcome so that the batik industry can maintain its existence. One of the possible solutions is to understand buying behavior characteristics of the existing consumer groups, which are Millennials and gen Z. Therefore, the purpose of this research is to use a theoretical framework based on the Planned Behavior Theory (TPB) model by Ajzen (1991) to analyze the relationship between experimental variables and the effect on Indonesian Millennials and Gen Z's intention to buy Batik. The focus area selected was Java Island because that is an area with the largest batik industry center in Indonesia. So, the potential to reach a larger consumer need to be explored. Considering the potential of the new generation's high buying power, Millennials and Gen Z were selected as the subject of this study. A total of 177 respondents from various provinces in Java were involved in filling out an online questionnaire containing measurement items related to the purpose of this study. The next step is processing the data using the Partial Least Square Structural Equation Model (PLS-SEM), which has been widely used in various research disciplines over the last two decades. The results show that the five of six hypotheses tested are acceptable: 1) Attitude towards behavior influences purchase intention; (2) Batik Brand Image influences Attitude towards behavior; (3) Perceived behavior control influences purchase intention; (4) Subjective norm influences purchase intention; (5) attitude mediates the relationship between brand image and purchase intention.